Novel selective medium for the isolation of corynebacterium kroppenstedtii from heavily colonised clinical specimens. Issue 9 (28th March 2018) - Wong, Sally Cheuk Ying; Poon, Rosana W S; Foo, Chuen-Hing; Ngan, Antonio H Y; Tse, Herman; Lam, Vivian C M; Leung, Tiffany H Y; Wong, Chun-Pong; Cheng, Vincent C C; Chen, Jonathan H K; Yuen, Kwok-Yung
Abstract : Aims: Granulomatous mastitis due to Corynebacterium kroppenstedtii is an increasingly recognised cause of an indolent and distressing mastitis in non-lactating females. This slow-growing lipophilic organism is not reliably isolated using routine culture methods. A novel selective culture medium (CKSM) is designed to optimise the isolation of this organism from clinical specimens. Methods: CKSM contains 10% galactose and Tween 80 (10%) to enhance the growth of C. kroppenstedtii, fosfomycin (100 µg/mL) to suppress the other bacteria, and differentiate C. kroppenstedtii from non- kroppenstedtii lipophilic corynebacteria by esculin hydrolysis. The medium was evaluated for its ability to support the growth of C. kroppenstedtii, selection and differentiation of C. kroppenstedtii from other bacteria in non-sterile clinical specimens. Results: C. kroppenstedtii grew as 1–2 mm colonies with black halo on CKSM within 72 hours of incubation, compared with barely visible pinpoint colonies on routine blood agars. During the four-month period of evaluation with 8896 respiratory specimens, 103 breast specimens, 1903 female genital tract specimens, 617 newborn surface swabs and 10 011 miscellaneous specimens, 186 C. kroppenstedtii were isolated, including 127 (1.4%) respiratory and 59 (0.5%) miscellaneous specimens, 184 of them were found only on CKSM. Besides the three (2.9%) positive breast specimens, 27 (1.4%) high vaginal and endocervical swabs, and 11 (1.8%) surface swabs of newborns were positive for C. kroppenstedtii . Conclusions: CKSM is a useful addition to routine agar media for the isolation of C. kroppenstedtii, and will be helpful for studying the epidemiology and transmission of this unusual Corynebacterium causing granulomatous mastitis.